Numerical Study on the Tandem Submerged Hydrofoils Using RANS Solver. (10th February 2021) - Maram, Moloud Arian; Ghafari, Hamid Reza; Ghassemi, Hassan; Ghiasi, Mahmoud
Abstract : This paper is presented on the tandem two-dimensional hydrofoils with profiles NACA4412 in single-phase and two-phase flow domains for different submergence depths and different distances in a various angle of attack (AoA). Also, supercavitation is studied at σ = 0.34 by the Zwart cavitation model. Reynolds-averaged Navier–Stokes (RANS) with the shear stress transport (SST) K-ω is employed as a turbulence model in transient analysis of Ansys FLUENT software. The numerical results show that, by increasing depth, the drag coefficient increases for both hydrofoils 1 and 2 as well as the lift coefficient. The drag coefficient of hydrofoil 2 is bigger than hydrofoil 1 for all depths; moreover, it was found that the flow pressure behind the hydrofoil 1 had affected the upper and the lower surface of the hydrofoil 2 at each distance or AoA. These effects are observed in the hydrofoil 2 lift coefficient as well as the flow separation. However, the maximum lift-to-drag ratio is observed at AoA = 8 ° and 3.5c distance. Also, single-phase results reveal that the value of pressure and the hydrodynamic coefficient are very different from the two-phase flow results, due to the elimination of the free surface. So, a two-phase flow domain is recommended for increasing the accuracy of results. In addition, the investigation of supercavitation shows a growth in cavity occurrence on the surface by raising AoA.